2021
DOI: 10.21203/rs.3.rs-139872/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chinese Herbal Preparation SaiLuoTong Alleviates Brain Ischemia Via Nrf2 Antioxidation Pathway Dependent Cerebral Microvascular Protection

Abstract: Background: Stroke is one of the most devastating diseases worldwide. Chinese herbal preparation SaiLuoTong capsule (SLT) showed outstanding therapeutic effects over stroke and its sequelae. This study is to elucidate the mechanism. Methods: We duplicated cerebral ischemia model in rats by permanent MCAO, and simulated ischemia injury in cultured hCMEC/D3 cells with oxygen and glucose deprivation/reoxia (OGD/R); we treated them with SLT. Brain infarction volumes and micromorphology were examined with TTC and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 46 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…Another study found that pretreatment with CR followed by I/R (2 h hypoxia, 4 h reoxygenation) protected myocardial ischemic injury and regulated autophagy AMP-activated protein kinase (AMPK) mechanistic pathway (Zeng et al, 2016). Fan et al (2021) showed CR protected myocardial mitochondria injury and acute myocardial infarction in rats (Leijiao Fan, 2021b). CR (15 and 30 mg/kg) significantly attenuated mitochondrial damage by increasing the membrane potential and reducing the mitochondrial permeability transition pore openness.…”
Section: Cardiovascular Protectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study found that pretreatment with CR followed by I/R (2 h hypoxia, 4 h reoxygenation) protected myocardial ischemic injury and regulated autophagy AMP-activated protein kinase (AMPK) mechanistic pathway (Zeng et al, 2016). Fan et al (2021) showed CR protected myocardial mitochondria injury and acute myocardial infarction in rats (Leijiao Fan, 2021b). CR (15 and 30 mg/kg) significantly attenuated mitochondrial damage by increasing the membrane potential and reducing the mitochondrial permeability transition pore openness.…”
Section: Cardiovascular Protectionmentioning
confidence: 99%
“…Due to the limitations of the aforementioned therapies, there have been continuing efforts to discover, develop, research, and implement new therapies for IS (Marquez-Romero et al, 2020;Williams et al, 2020). A number of natural ingredients and traditional herbal medicines have been investigated as potential therapies for IS, including ginsenoside Rg1 and Rb1 (Gao, Bai et al, 2020), Naoxinqing (NXQ) (Bei et al, 2004), Buyang Huanwu Decoction (Hao et al, 2012), saffron (SF) (Sharma et al, 2020) and related formulas including Naodesheng (Sugawara and Chan, 2003;Hao et al, 2015), Weinaokang (Zhang et al, 2010), also known as Sailoutong (SLT) (Fan et al, 2021). SLT is a standardized combination of SF that has been shown to be effective for vascular dementia in Phase I and Phase II clinical trials and is currently under the phase III trial for vascular dementia (Chang et al, 2016;Jia et al, 2018;Steiner et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation